2013
DOI: 10.1136/emermed-2012-201472
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and practices regarding resuscitation in emergency departments in Trinidad and Tobago

Abstract: BackgroundEthical issues with regard to resuscitation are increasingly important. Understanding how emergency physicians deal with these problems is essential for the development of policies for resuscitative care.ObjectivesTo identify the knowledge, opinions and practices of emergency physicians employed full time in public hospitals in Trinidad and Tobago, with respect to cardiopulmonary resuscitation. To compare the differences in responses between physicians in training and those who were not. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Similar to many previous studies, the results obtained from our study revealed that FPDR is associated with increased fear of litigation, particularly among Tabriz Medical University’s physicians. This could explain these physicians’ aversion to FPDR [ 13 ]. However, considering the results of Jabre et al’s study, physicians should cast aside their fear of medico-legal claims when performing family-witnessed CPR in their daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to many previous studies, the results obtained from our study revealed that FPDR is associated with increased fear of litigation, particularly among Tabriz Medical University’s physicians. This could explain these physicians’ aversion to FPDR [ 13 ]. However, considering the results of Jabre et al’s study, physicians should cast aside their fear of medico-legal claims when performing family-witnessed CPR in their daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, we must not stop considering the risks and complications. 3,4 Healthcare staff often find themselves in situations where a reflection and a decision is a process between different disciplines, such as law, philosophy, anthropology and not just medicine and nursing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, relevant questions on KAB were designed based on multiple previous studies concerning similar topics. [7][8][9][10] Evaluation of the questionnaire's internal consistency was performed using Cronbach's alpha.…”
Section: Questionnaire Toolmentioning
confidence: 99%